(The causal relationship between Saudi women's empowerment and economic growth (mid-2015-1999 - Al-Juaid, Shoq Habab (Journal of Economic, Administrative and Legal Sciences, 2019)
This research aims to identify the effect of the economic empowerment of Saudi women on economic growth during the period (1990 - 2015). The researcher used the descriptive analytical method. In its study, it adopted the standard methods of unit root testing to test the stability of time series. The results of the test showed that the time series of the variables studied were first-class. The results found that there was a relationship between economic growth and the proportion of girls in general education in the long term. The results also showed a relationship between economic growth and dependency ratio in the long term. Gangerger's causality test showed a positive, one-way relationship between economic growth and the proportion of girls in public education in the long run, indicating that economic growth affects the increase in girls 'education, while girls' education does not affect economic growth. The results did not show any statistically significant relationship between economic growth and women's participation in the labor market. In light of these results, the study presented a number of recommendations, the most important of which are: To find the best ways to activate the vision of 2030, especially the items related to empowering women and raising their contribution to the GDP; opening the fields for women to have their own work through raising awareness among the community; Education and workshops for women, and abandon the legacy that hinders women's work and participation in economic life.
Keywords: economic empowerment; empowerment of women; Saudi women; economic growth